1971
DOI: 10.1037/h0031514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of videotape modeling and self-confrontation techniques on microcounseling behavior.

Abstract: This investigation evaluates the effects of videotape modeling and videotape feedback techniques on the counseling behavior of untrained female undergraduates in a quasi-therapy, microcounseling, situation. Their performances were compared to those of control trainees who were given only a written description of the counseling skills in question, emphasizing attention to client feelings. Each trainee (# = 42) briefly counseled a volunteer client three separate times with intervening training periods. Judges ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Very few studies reported conforming to the latter two guidelines. Many studies also failed to observe the first two precautions, or failed to check reliability at all, or reported low (i.e., less than .75) reliability coefficients on some (Bailey, Deardorf, & Nay, 1977;Berenson, Carkhuff, & Myrus, 1966;DiMattie & Arndt, 1974;Dooley, 1975;Frankel, 1971;Ivey, Normington, Miller, Morrill, & Haase, 1968;Lambert, 1974;Martin & Carkhuff, 1968;Perry, 1975;Rappaport, Gross, & Lepper, 1973;Ryan & Budner, 1970;Selfridge, Weitz, Abramowitz, Calabria, Abramowitz, & Steger, 1975) or on all dependent variables data (Blane, 1968;Canada, 1973;Carkhuff & Truax, 1965;Carlson, 1974;Carter & Pappas, 1975;Delaney, Long, Masucci, & Moses, 1969;Dowd & Blocher, 1974;Gade & Matuschka, 1973;Hountras & Redding, 1969;Kanfer & Pomeranz, 1965;Kingdon, 1975;Kuna, 1975;Miller, Morrill, Ivey, Normington, & Uhleman, 1973;Miller, Morrill, & Uhleman, 1970;Ornston, Cicchetti, & Towbin, 1970;Roark, 1969;Saltmarsh & Hubele, 1974;Schoch, 1966;Silverman & Quinn, 1974;Ward, Kagan, & Krathwohl, 1972;Werner & Schneider, 1974).…”
Section: Observer Frequency Counts and Ratingsmentioning
confidence: 95%
See 2 more Smart Citations
“…Very few studies reported conforming to the latter two guidelines. Many studies also failed to observe the first two precautions, or failed to check reliability at all, or reported low (i.e., less than .75) reliability coefficients on some (Bailey, Deardorf, & Nay, 1977;Berenson, Carkhuff, & Myrus, 1966;DiMattie & Arndt, 1974;Dooley, 1975;Frankel, 1971;Ivey, Normington, Miller, Morrill, & Haase, 1968;Lambert, 1974;Martin & Carkhuff, 1968;Perry, 1975;Rappaport, Gross, & Lepper, 1973;Ryan & Budner, 1970;Selfridge, Weitz, Abramowitz, Calabria, Abramowitz, & Steger, 1975) or on all dependent variables data (Blane, 1968;Canada, 1973;Carkhuff & Truax, 1965;Carlson, 1974;Carter & Pappas, 1975;Delaney, Long, Masucci, & Moses, 1969;Dowd & Blocher, 1974;Gade & Matuschka, 1973;Hountras & Redding, 1969;Kanfer & Pomeranz, 1965;Kingdon, 1975;Kuna, 1975;Miller, Morrill, Ivey, Normington, & Uhleman, 1973;Miller, Morrill, & Uhleman, 1970;Ornston, Cicchetti, & Towbin, 1970;Roark, 1969;Saltmarsh & Hubele, 1974;Schoch, 1966;Silverman & Quinn, 1974;Ward, Kagan, & Krathwohl, 1972;Werner & Schneider, 1974).…”
Section: Observer Frequency Counts and Ratingsmentioning
confidence: 95%
“…However, the remaining 19 training studies dealt with undergraduate experimental subjects as trainees (Bailey et al, 1977;Berenson et al, 1966;Dalton et al, 1973;DiMattia & Zimmer, 1972;Frankel, 1971; E. Goldberg, 1971;Kanfer & Pomeranz, 1965;G. Kelly, 1973;O'Connell, 1974;Payne & Gralinski, 1968;Payne, Weiss, & Knapp, 1972;Payne, Winter, & Ball, 1972;Rappaport et al, 1973;Reddy, 1969aReddy, , 1969bShoemaker, 1973;Stone & Stein, 1978;Toukmanian & Rennie, 1975;Uhlemann, Lea, & Stone, 1976).…”
Section: Research Subjects (Trainees)mentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, planned use of models offers an especially efficient method for training educational, counseling, or other child-handling skills to naive clients, such as institutional attendants (Gardner, 1972), teacher trainees (Haring & Fargo, 1969), parents (Bernal, Duryee, Pruett, & Burns, 1968;Seitz & Terdal, 1972), and counselor trainees (Frankel, 1971 ). When the teaching objective is for students to learn to perform rather than to verbalize principles, there is evidence (Gardner, 1972) for the superiority of modeling plus guided practice over lectures plus class participation and discussion.…”
Section: Change-agent Educationmentioning
confidence: 97%
“…With regard to the video feedback for counsellor trainees, Frankel (1971) feels that it can be an important adjunct to conventional training for counsellors; counsellor trainees, after viewing videotapes of their interviews, tend to change their self perceptions, gain in confidence and in awareness of personal qualities and experience an increased desire for further self study.…”
Section: Feedback As a Valuable Acquisitionmentioning
confidence: 99%